2009
DOI: 10.1111/j.1365-246x.2008.04027.x
|View full text |Cite
|
Sign up to set email alerts
|

The shear wave velocity underneath Bucharest city, Romania, from the analysis of Love waves

Abstract: S U M M A R YFrom the dispersion of Love waves, we infer models of shear wave velocity structure underneath Bucharest (Romania) at depths down to 2 km that can contribute to seismic hazard estimation. Waves from eight regional events recorded during 10 months with a network of 34 seismic broad-band stations of the URban Seismology (URS) experiment are used. Although these events provide poor azimuthal coverage the data reliably constrain a shear wave velocity model with an interface between the Neogene and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…For this stacking, the recordings of the respective events were normalized by their total recorded energy. The comparison with the Love wave dispersion curves obtained from ambient vibrations (Manea et al 2016) and with the ones proposed by Sèbe et al (2009) shows a good agreement (Fig. 5 left).…”
Section: Surface Wave Dispersion and Ellipticitysupporting
confidence: 73%
See 1 more Smart Citation
“…For this stacking, the recordings of the respective events were normalized by their total recorded energy. The comparison with the Love wave dispersion curves obtained from ambient vibrations (Manea et al 2016) and with the ones proposed by Sèbe et al (2009) shows a good agreement (Fig. 5 left).…”
Section: Surface Wave Dispersion and Ellipticitysupporting
confidence: 73%
“…For the first event (Fig. 3, left), an intermediatedepth event that occurred in the Vrancea area (021), the energy is distributed between 0.5 and 6 Hz and is not generating surface waves due to the large focal depth (Sèbe et al 2009). Conversely, for the regional shallow event located on Bulgarian territory (351), surface waves at low frequencies strongly dominate the signal (Fig.…”
Section: Time-frequency Analysis Of Earthquake Recordingsmentioning
confidence: 99%
“…An amplitude and site effect study by Sudhaus & Ritter (2009), using waveforms of the URS data set, found the same effect of latitude‐dependent ground motion amplification across the Bucharest area. Sudhaus & Ritter (2009) relate this effect to resonance effects in the unconsolidated sediments above the distinct dipping Neogene–Cretaceous boundary from 800 m depth in the south to 2000 m depth in the north (Mandrescu et al 2004; Sèbe et al 2009). Also for the URS data set Ziehm (2006) applied a comprehensive H/V analysis for the Bucharest area.…”
Section: Resultsmentioning
confidence: 99%
“…There is only one value of Fourier phase at each frequency. In cases where multiple overtones interfere in the seismogram, phase-matched filter techniques can be used to isolate a single mode in the waveform signal (Herrin & Goforth 1977;Russell et al 1988;Sèbe et al 2009). These techniques essentially apply a deconvolution with a reference dispersion pref(f ) in order to concentrate the seismic energy of the respective mode in a small time window.…”
Section: Methods Of Dispersion Analysis Failmentioning
confidence: 99%